Consumer culture theory - Belk, Russell W.; Price, Linda; Peñaloza, Lena (Emerald, 2013)
In the latest volume of Research in consumer behavior : Consumer culture theory, the series contains a selection of edited best papers from the Eighth Consumer Culture Theory Conference held in Tucson, Arizona in June, 2013. These papers represent the latest ethnographic and qualitative research on consumption and consumer culture from scholars around the world. These studies in this volume draw on an array of largely qualitative methodologies including ethnography, netnography, autoethnography, discourse analysis, phenomenology, and semiotics. These diverse approaches to consumer research complement each other and provide a cutting edge view of consumer research.
Includes index.
Keywords: Consumer behavior.; elektronické knihy; electronic books